Estimation of Subsurface Structure Using Euler Deconvolution and SVD Methods of Geomagnetic Data in the Non-Volcanic Geothermal Area of Tahi Ite Village, Bombana, Southeast Sulawesi, Indonesia - Rani Chahyani; Manan, Abdul (UIR PRESS, 2026)
This study aims to estimate the presence of subsurface structures in the geothermal area of ​​Tahi Ite Village, Bombana Regency, Southeast Sulawesi by using geomagnetic data collected in the field at 656 measurement points using a PPM unit divided into nine survey lines oriented N0oS, with distances between measurement points and between survey lines of approximately 50 m and 180 m, respectively. Based on the research results, the Total Magnetic Intensity (TMI) values for the study area ranged from 42,375.605 to 42,817.045 nT. A value range of 441.44 nT indicates the presence of rock magnetic heterogeneity in the geothermal manifestation area. After applying Diurnal Correction and IGRF Correction, the Total Magnetic Anomaly (TMA) values were found to be approximately -136.89 to 200 nT. The Local Magnetic Anomaly (LMA) was obtained after performing an upward continuation process through four continuation stages up to an altitude of 1,700 m from the reference surface, The Local Magnetic Anomaly (LMA) was obtained after performing an upward continuation process through four continuation stages up to a height of 1,700 m from the reference surface, and was found to be within a range of approximately -120 to 60 nT. Subsequently, Reduced to the Pole (RTP) processing was applied to transform the magnetic response so that it lies above its causative source and exhibits a monopolar nature. On the RTP results, the Euler Deconvolution (DE) method with a Structural Index of N=0 and the Second Vertical Derivative (SVD) method were applied to infer the presence of subsurface structures. The results show the presence of magnetic anomaly patterns suggesting strong structural control with a dominant North–South orientation. It is estimated that there are approximately five to nine minor faults with depths ranging from <15 m (Very Shallow) to >55 m (Deep), and it is known that approximately two minor faults intersect the Tahi Ite hot spring. The existence of these minor faults is thought to act as thermal conduction pathways and channels for the migration of hydrothermal fluids to the surface with the water source in the reservoir originating from surface or meteoric water. These findings are also supported by the presence of outcrops, further confirming that the Tahi Ite Village geothermal system is non-volcanic in nature and controlled by secondary structures in the form of minor faults.